KERAGAAN MOLEKULAR AREN SUMATERA UTARA DAN AREN SULAWESI TENGGARA BERDASARKAN PRIMER OPD-20 DAN OPH-06 - Lollie Agustina P. Putri; Giovana; M. Basyuni; Mahyuni K. Harahap (Talenta Publisher, 2016)
This study aims to determine patterns of kinship based on the molecular nature palm plant populations from North Sumatra (South Tapanuli) and Southeast Sulawesi using Random Amplified Polymorphic DNA markers (RAPD). Each of these ten individuals aren natural populations from North Sumatra and Southeast Sulawesi origin have been analyzed with the molecular-based primer OPD 2-20 and OPH-06. The results indicate the formation of three groups, namely the group 1 is formed of people from North Sumatra, group 3 is formed of sugar origin Southeast Sulawesi, while the second group is formed of two palm from North Sumatra and Southeast Sulawesi.